2017
DOI: 10.1002/icd.2066
|View full text |Cite
|
Sign up to set email alerts
|

Executive attention at 8 years: Concurrent and longitudinal predictors and individual differences

Abstract: Executive attention, the attention necessary to reconcile conflict among simultaneous attentional demands, is vital to children's daily lives. This attention develops rapidly as the anterior cingulate cortex and prefrontal areas mature during early and middle childhood. However, the developmental course of executive attention is not uniform amongst children. Therefore, the purpose of this investigation was to examine the role of individual differences in the development of executive attention by exploring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…As well, the speed of visual information processing in infancy predicts a variety of executive functions in childhood ( Rose et al, 2012 ). More specifically, infants’ attentional focus has been demonstrated to be a crucial predictive factor for later executive functions ( Joyce et al, 2018 ), and also has been shown to predict later self-regulatory behavior ( Johansson et al, 2015 ). These findings suggest that the early ability to control focused attention has individual stability and longitudinal predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…As well, the speed of visual information processing in infancy predicts a variety of executive functions in childhood ( Rose et al, 2012 ). More specifically, infants’ attentional focus has been demonstrated to be a crucial predictive factor for later executive functions ( Joyce et al, 2018 ), and also has been shown to predict later self-regulatory behavior ( Johansson et al, 2015 ). These findings suggest that the early ability to control focused attention has individual stability and longitudinal predictive value.…”
Section: Discussionmentioning
confidence: 99%